Pengaruh Motivasi Kerja Terhadap Kinerja Penyuluh Pertanian Lapangan - Faiz Adiansyahputra Mahulauw; Stephen Frans William Thenu; Jeter Donald Siwalette (Jurnal Indonesia Sosial Teknologi, 2023)
This study aimed to identify the characteristics of PPL in the Salahutu sub-district and to analyze the effect of work motivation on the performance of agricultural extension workers in the Central Maluku district. The study consisted of 9 variables, namely the Performance of Extension Officers X1 Leadership, X2 Work Environment, X3: Intensive or Operational Costs X4 Work Culture, X5 Communication, X6 Salary, X7 Training, X8 Awards, X9 Age factor, which was analyzed using the Multiple Linear Regression Method with assistance SPSS Version 23.0. The study results show that all of these variables jointly affect the performance of agricultural extension workers (PPL). seven variables have a positive and significant effect on paddy rice production. In contrast, the training and reward variables have a positive and insignificant relationship to the performance of field agricultural extension workers (PPL).